Malonate-based inhibitors of mammalian serine racemase: kinetic characterization and structure-based computational study - Vorlová, Barbora; Nachtigallová, Dana; Jirásková-Vaníčková, Jana; Ajani, Haresh; Jansa, Petr; Rezáč, Jan; Fanfrlík, Jindřich; Otyepka, Michal; Hobza, Pavel; Konvalinka, Jan; Lepšík, Martin (European journal of medicinal chemistry, 2015)
Overactivation of NMDA receptors has been implicated in various neuropathological conditions, including brain ischaemia, neurodegenerative disorders and epilepsy. Production of d-serine, an NMDA receptor co-agonist, from l-serine is catalyzed in vivo by the pyridoxal-5'-phosphate (PLP)-dependent enzyme serine racemase. Specific inhibition of this enzyme has been proposed as a promising strategy for treatment of neurological conditions caused by NMDA receptor dysfunction. Here we present the synthesis and activity analysis of a series of malonate-based inhibitors of mouse serine racemase (mSR). The compounds possessed IC50 values ranging from 40 ± 11 mM for 2,2-bis(hydroxymethyl)malonate down to 57 ± 1 μM for 2,2-dichloromalonate, the most effective competitive mSR inhibitor known to date. The structure-activity relationship of the whole series in the human orthologue (hSR) was interpreted using Glide docking, WaterMap analysis of hydration and quantum mechanical calculations based on the X-ray structure of the hSR/malonate complex. Docking into the hSR active site with three thermodynamically favourable water molecules was able to discern qualitatively between good and weak inhibitors. Further improvement in ranking was obtained using advanced PM6-D3H4X/COSMO semiempirical quantum mechanics-based scoring which distinguished between the compounds with IC50 better/worse than 2 mM. We have thus not only found a new potent hSR inhibitor but also worked out a computer-assisted protocol to rationalize the binding affinity which will thus aid in search for more effective SR inhibitors. Novel, potent hSR inhibitors may represent interesting research tools as well as drug candidates for treatment of diseases associated with NMDA receptor overactivation.
Keywords: Animals; vztah mezi dávkou a účinkem léčiva; Kinetics; racemasy a epimerasy; Molecular Structure; Enzyme Inhibitors; Structure-Activity Relationship; Mice; Racemases and Epimerases; myši; krystalografie rentgenová; Models, Molecular; molekulární struktura; Dose-Response Relationship, Drug; molekulární modely; inhibitory enzymů; Thermodynamics; malonáty; vztahy mezi strukturou a aktivitou; zvířata; Crystallography, X-Ray; termodynamika; Malonates; kinetika